ANALISIS KEBIJAKAN PENDIDIKAN GRATIS DI SEKOLAH MENENGAH ATAS DALAM KAITANNYA DENGAN KUALITAS PENDIDIKAN MENENGAH ATAS - Suyahman Suyahman (Jurnal Pendidikan Kewarganegaraan, 2016)
Writing this article aims to describe the Free Education Policy Analysis At High School In Relation With Education Quality SMA. This article is a scientific work that is done by using the approach of literature that examines the books, literature-Literatu, research journals related to the topic of the article the author writes, the data collection methods were used that documentation, the data analysis technique interactive techniques comprising of 3 stages: data reduction, data display and data verification. The results showed that the policy of free education in high school is less on target for implementation is not selective. This policy should only intended for students who are economically poor but have great potential. This policy has nothing to do with improving the quality of learning. Due to this policy no challenge for the students to study harder, as well as for the teachers nor the effort to reorganize the learning process more qualified. This is due to the absence of proactive parents toward school, lack of harmonization of interaction between teachers and parents, because the parents assumption that free education means free everything. The conclusion of this article is necessary reconsideration existent essence and school policy for high school students. And it should also be followed keasadarn teachers to improve the quality of learning. Keywords: free schools and improving the quality of learning.